Brain Response and Reaction Time in Natural and Comfort Conditions, with Energy-Saving Potential in an Office Environment - Wiwik Budiawan (MDPI AG, 2021)
Psychological adaptation to ambient temperatures is fascinating and critical, both theoretically and practically, for energy efficiency in temperate climates. In this study, we investigated and compared the brain response (event-related potentials with a late positive component and latency ~300 milliseconds; labeled “P300” in the present study) and reaction times of Indonesian participants (n = 11), as tropical natives living in Japan, and Japanese participants (n = 9) in natural (i.e., hot during the summer and cold during the winter) and comfort conditions (with cooling and heating). Thermal comfort under contrasting conditions was studied using both instruments and subjective ratings. P300 potential and reaction time were measured before and after a Uchida–Kraepelin (U–K) test (30 summation lines). The results showed that P300 potential and latency did not change between the pre- and post-U–K test among conditions in any of the groups. Furthermore, Indonesian participants showed lower P300 potential (hot conditions) and slower P300 latency (hot and cooling conditions) than Japanese participants. We also found that the reaction time of the Indonesian group significantly differed between the pre- and post-U–K test in an air-conditioned environment, with either cooling or heating. In this study, Indonesian participants demonstrated a resistance to P300 and worse reaction times during work in a thermally unfamiliar season, specifically indicated by the indifferent performances among contrasting environmental conditions. Indonesian participants also showed similar thermal and comfort sensations to Japanese participants among the conditions. In the winter, when the Indonesian neutral temperature is higher than Japanese’s, the energy consumption may increase.